Molecular folding governs switchable singlet oxygen photoproduction in porphyrin-decorated bistable rotaxanes - Riebe, Jan (2024)
Rotaxanes are mechanically interlocked molecules where a ring (macrocycle) is threaded onto a linearmolecule (thread). The position of the macrocycle on different stations on the thread can be controlledin response to external stimuli, making rotaxanes applicable as molecular switches. Here we show that bistable rotaxanes based on the combination of a Zn(II) tetraphenylporphyrin photosensitizer,attached to the macrocycle, and a black-hole-quencher, attached to the thread, are capable of singletoxygen production which can be switched on/off by the addition of base/acid. However, we found thatonly a sufficiently long linker between both stations on the thread enabled switchability, and that thedirection of switching was inversed with regard to the original design. This unexpected behavior wasattributed to intramolecular folding of the rotaxanes, as indicated by extensive theoretical calculations.This evidences the importance to take into account the conformational flexibility of large molecularstructures when designing functional switchable systems.